PENINGKATAN LEARNING ENGAGEMENT PADA PELATIHAN BERBASIS KOMPOTENSI MELALUI PLATFORM PEMBELAJARAN ONLINE DAN ARTIFICIAL INTELLIGENCE (AI) DI BBPK MAKASSAR: ID - Awaluddin, Muminah (Balai Besar Pelatihan Kesehatan (BBPK) Makassar, 2023)
The main challenge in the training sector is the implementation of education and training which is shifting from traditional/classical methods to online learning. Currently there is a shift in training methods from classical/face-to-face training to online training and blended learning using learning technology.The research aims to get ideas related to effective learning in order to increase learning engagement in training in the era of society 5.0. This research method is narrative review. Referring to journal article references with the theme of learning in the era of society 5.0, learning engagement theory & andragogy and learning strategies in blended learning training. Research result ; To get the connection between Learning Engagement & Andragogy Learning in training, it needs to be formulated including delivery strategies and multimedia selection so that learning engagement can be realized and remains based on POD principles. Learning strategies in blended learning training; The facilitator must explain the learning objectives, competencies to be achieved and make modifications to several class components. Creating Collaborative activities; Virtual face-to-face (Synchronous virtual) is used to discuss the learning experiences of each participant, in online learning conditions. Two important things are learning materials (Course materials) and (technological tools). The strategies for the types of learning platforms used at BBPK Makassar are: MOOC (Massive Open Online Course); Virtual Learning/Online; Classical/Offline. Other alternative learning media to increase learning engagement are Gamification learning media, AI-based learning videos, Virtual Reality-based learning. Conclusion: Learning agility in the current era of society 5.0 allows everyone to carry out learning anytime and anywhere. This condition causes the training design to move more towards online and blended learning. To increase learning engagement, it is necessary to pay attention to andragogy/Adult Learning (POD) learning design. Andragogy/POD in online/blended based training is very influential in increasing learning enthusiasm, participation and internal motivation of students/trainees. Keywords : Virtual Reality, Andragogy, Adult learning, Artificial Intelegence (AI)